PEMBERDAYAAN KADER PKK UNTUK MEMBANTU PENDATAAN KEPEMILIKAN AKTA KELAHIRAN: STUDI PADA PELAYANAN KEPENDUDUKAN KELURAHAN KIDUL DALEM, KECAMATAN KLOJEN, KOTA MALANG - Lely Indah Mindarti; Nur Fauziah (Pusat Studi Kependudukan dan Kebijakan, Universitas Gadjah Mada, 2016)
Service provider must provide public service, such as birth certi cate, to the society. However, people in Kidul Dalem Village, Malang were still unaware of its importance. Empowerment Family Welfare Program (PKK) cadres of Kidul Dalem Village was expected to increase the function and role of those cadres (women) performing the public service. This research was a descriptive research with qualitative approach and using observation, interview and documentation techniques for collecting the data. The interactive model of Miles and Huberman was used for data analyzing. This study showed the empowerment program of PKK cadres in collecting data of birth certi cate ownership was a collaboration of Department of Population and Civil Registration of Malang City. This program helped to increase the society awareness on the importance of birth certi cate ownership that could be seen from the numerous application letters of birth certi cate in the village of ce.